Ag2ZnSnS4–ZnS core–shell colloidal quantum dots: a near-infrared luminescent material based on environmentally friendly elements. Issue 17 (15th April 2021) - Saha, Avijit; Konstantatos, Gerasimos
Abstract : Passivation and optimization of luminescent AZTS QDs with ZnS shells gave rise to a ∼30-fold increase in the PLQY results in RoHS compliant low-cost, bright and tunable NIR-luminescent phosphors for bio-imaging and LED applications. Abstract : Low cost, multinary colloidal quantum dots (QDs) based on environmentally friendly elements, with bright, narrow-width, tunable near-infrared (NIR) luminescence are promising alternatives to Cd and Pb chalcogenide QDs for in vivo bio-imaging, LED and sensing applications. Herein, we demonstrate Pb/Cd free solution-processed colloidal luminescent Ag2 ZnSnS4 –ZnS (AZTS–ZnS) core–shell QDs with precise control over the ZnS shell thickness and thereby its optical properties. Unlike indium based multinary (I–III–VI group) core–shell QDs these nanocrystals show a narrow photoluminescence (PL) full width at half maximum (fwhm) of 105–110 meV in the first NIR window. By monitoring the starting AZTS core size, we achieve tunable emission over a small NIR window in these QDs with the best PL quantum yield (PLQY) of 17.4%.